Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/9181836
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of V2V Messages for Car-Following Behavior with the Traffic Jerk Effect

Abstract: The existing model of sudden acceleration changes, referred to as the traffic jerk effect, is mostly based on theoretical hypotheses, and previous research has mainly focused on traditional traffic flow. To this end, this paper investigates the change in the traffic jerk effect between inactive and active vehicle-to-vehicle (V2V) communications based on field experimental data. Data mining results show that the correlation between the jerk effect and the driving behavior increases by 50.6% on average when V2V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Moreover, the total value of the subject during the time period t 1 ∼ t n can be calculated by Formula (26). The total value of the object during the time period t 1 ∼ t n can be calculated by Formula (27):…”
Section: Transportation Utility Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the total value of the subject during the time period t 1 ∼ t n can be calculated by Formula (26). The total value of the object during the time period t 1 ∼ t n can be calculated by Formula (27):…”
Section: Transportation Utility Methodsmentioning
confidence: 99%
“…Xylia et al (2019) [26] introduced charging technologies based on the project experiences in the Nordic countries of the EU and indicated that these technologies could reduce the maintenance costs of PT infrastructure. Li et al (2020) [27] estimated the jerk effect changes under two vehicle-to-vehicle communications based on experimental data and proposed a car-following model to improve traffic flow stability for PT systems. Sheikh et al (2020) [28] proposed an automatic traffic incident detection technique based on vehicle to infrastructure communications to monitor PT scenarios.…”
Section: Public Transportationmentioning
confidence: 99%
“…Due to development of intelligent transportation technology and vehicle to vehicle (V2V) environment technology, the vehicles are equipped with intelligent devices while moving [35,36] and drivers can obtain information regarding surrounding vehicles more accurately and widely (see figure 1). This has lead to the development of various car-following models based on information interaction between vehicles to obtain information regarding multi-vehicle average velocity, average anticipative velocity, average headway, etc [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng Liang et al [17] developed a safety rule-based cellular autonomous driving model (CA) in a V2V environment. Based on real V2V following experimental data, [18] proposed an extended following model based on the FVD following model, which describes the phenomenon of dramatic fluctuations in acceleration of the vehicle while receiving information. The above study performs the representation of vehicle following state in the connected vehicle environment and demonstrates more systematically that CVs can significantly improve the safety and energy efficiency of vehicle operation.…”
Section: Introductionmentioning
confidence: 99%